2019
DOI: 10.1210/endocr/bqz022
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Inhibition of DNA Methylation Disrupts Testosterone-Dependent Masculinization of Neurochemical Phenotype

Abstract: Many neural sex differences are differences in the number of neurons of a particular phenotype. For example, male rodents have more calbindin-expressing neurons in the medial preoptic area (mPOA) and bed nucleus of the stria terminalis (BNST), and females have more neurons expressing estrogen receptor alpha (ERα) and kisspeptin in the ventromedial nucleus of the hypothalamus (VMH) and the anteroventral periventricular nucleus (AVPV), respectively. These sex differences depend on neonatal exposure to testostero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Indeed, hormonal influences not only affect internal and external genital development and differentiation; the embryo's brain has also been shown to differentiate sexually [12][13][14], perhaps through control mechanisms similar to those developed by the external genitalia [15]. On the other hand, it is also possible that the induction of the central nervous system (CNS) by hormones affects the patterns of hormonal secretion and, consequently, sexual behavior in adults [16][17][18][19][20]. Thus, the sex of an individual and their sexual expression, i.e., homoor heterosexual, must be considered the result of all influences that the individual receives, both before and after birth [8].…”
Section: Determination and Differentiation Of The Human Sexmentioning
confidence: 99%
“…Indeed, hormonal influences not only affect internal and external genital development and differentiation; the embryo's brain has also been shown to differentiate sexually [12][13][14], perhaps through control mechanisms similar to those developed by the external genitalia [15]. On the other hand, it is also possible that the induction of the central nervous system (CNS) by hormones affects the patterns of hormonal secretion and, consequently, sexual behavior in adults [16][17][18][19][20]. Thus, the sex of an individual and their sexual expression, i.e., homoor heterosexual, must be considered the result of all influences that the individual receives, both before and after birth [8].…”
Section: Determination and Differentiation Of The Human Sexmentioning
confidence: 99%
“…Compared with postnatal males, postnatal female rats have higher DNA methyltransferase activity in the POA, which is followed by higher DNA methylation, and postnatal estradiol treatment reduced DNA methyltransferase activity and DNA methylation in the female POA (Nugent et al, 2015). Moreover, inhibition of DNA methyltransferase in the brain of neonatal females increased dendritic spines of POA neurons and masculinized sexual behavior (Nugent et al, 2015), and increased the number of Calb neurons in the CALB-SDN and CALB-BNSTp, resulting in elimination of the sex difference in Calb neurons (Mosley et al, 2017;Cisternas et al, 2020). Epigenetic regulation via histone modification also contributes to masculinization of the brain.…”
Section: Neuroestrogens Of Testicular Origin Are Significant Factors mentioning
confidence: 99%
“…Epigenetic modifications, such as DNA methylation, play prominent roles in the differentiation of cell type throughout the body and may underlie sexual differentiation of ERα neurons [12][13][14][15][16]. For example, we recently found that inhibiting DNA methylation in newborn mice reduces or eliminates the usual female bias in the number of neurons expressing ERα in the preoptic area and ventrolateral area of the ventromedial nucleus of the hypothalamus (VMHvl), which lies adjacent to the ARC [14,16].…”
Section: Introductionmentioning
confidence: 99%